Respon Pertumbuhan Semai Mahoni (Swietenia macrophylla King) pada Pot Organik dan Diinokulasi Fungi Mikoriza Arbuskula (FMA) - Sri Wilarso Budi; Faradila Mei Jayani (Jurnal Silvikultur Tropika, 2020)
A forest trees seedling production nowadays had used a polybag that caused the roots grow in a circle and the polybag are not easily degraded by the environment. It can be replaced with the use of container based on organic material that is environmentally friendly. The purposes of this study were to analyze the effect of treatment of raw material of organic pot and to analyze the inoculation of AMF to the growth of mahogany seedling as well. This study used the completely randomized design with two factor. The interaction of organic pot composition and the addition of AMF were significantly affected in terms of height and total dry weight of mahogany seedling. A single treatment of organic pot composition gave a significant effect on the increase of mahogany seedling diameter. A single treatment with AMF addition was significantly affected on the increase of both diameter and % mycorrhizal colonization at the root of mahogany seedling. The best treatment that has the greatest response of mahogany seedlings growth was the organic pot composition of newspaper:compost with a ratio of 3:2 along with the addition of AMF. Keywords: Arbuscular Mycorrhizal Fungi (AMF), inoculation, Mahogany (Swietenia macrophylla King), Organic Pot, seedling